Analisis Karakterisistik Sifat Tanah dalam Menilai Potensi Kesuburan Tanah di Dusun 13 Desa Bangun Sari Kecamatan Tanjung Morawa - Daniel Try; Agnes Enonita Harefa; Natalia Siagian; Anggita Lydia Sirait; Dini Sagala; Cahyani Oktavia Saragih; Mesi Tambunan; Qania Gultom; Ester Tinor Julianty Siagian; Stevanie Diva Marpaung (STKIP HARAPAN BIMA, 2026)
This study aims to analyze soil characteristics in assessing soil fertility potential in Hamlet 13, Bangun Sari Village, Tanjung Morawa District. The study employed a qualitative descriptive method through field observation and simple laboratory testing, including pH measurement (H?O and KCl), organic matter identification, carbonate testing using 10% HCl, and observation of soil physical and biological properties. Soil samples were collected directly from the study area and analyzed using descriptive interpretation to integrate physical, chemical, and biological aspects. Data were analyzed descriptively through the interpretation of observations and measurements of soil pH, carbonate reactions, and organic matter content to describe soil characteristics and fertility levels. The results showed that the soil had a brown color, clay to sandy clay texture, crumb structure, good drainage, and moderately loose consistency, with a pH ranging from 5 to 6, indicating slightly acidic conditions. Carbonate content was classified as low to moderate, while biological activity was indicated by the presence of plant roots and soil organisms such as earthworms. Overall, soil fertility was categorized as moderate, and improved organic matter management is needed to optimize agricultural potential in the study area.